PENGARUH BERMAIN PERAN TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN - Sholihah, Mar'atus; Syafe’i, Muhammad; Melani, Riza (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Developmental tasks that children need to possess include skills in interacting with their environment and expressing emotions positively, one of which is through role playing activities. This study aims to determine the effect of role-playing on the socio emotional development of children aged 5-6 years. This research is a quantitative quasi-experimental study with a non-equivalent control group design. The sample for this study consisted of 20 children aged 5-6 years at RA At Taqwa Trono, Klaten Regency. The data collection method was observation in the form of a checklist. Normality and homogeneity tests were conducted using the Kolmogorov-Smirnov and Levene's test for equality of variance. The data analysis in this study used parametric statistics. Hypothesis testing was performed using an independent samples t-test and a paired samples t-test with SPSS 22 for Windows. The data analysis results showed an increase in the mean pretest and posttest scores. The paired samples t-test results indicated that the significance value was < 0.05, meaning the data had a significant difference. Thus, it can be concluded that the use of role-playing influences the socio emotional development of children aged 5-6 years.